2018
DOI: 10.3390/ijms19113468
|View full text |Cite
|
Sign up to set email alerts
|

Agarwood Essential Oil Ameliorates Restrain Stress-Induced Anxiety and Depression by Inhibiting HPA Axis Hyperactivity

Abstract: In our previous investigation, we found that agarwood essential oil (AEO) has a sedative-hypnotic effect. Sedative-hypnotic drugs usually have an anxiolytic effect, where concomitant anxiety and depression are a common comorbidity. Therefore, this study further investigated the anxiolytic and antidepressant effects of AEO using a series of animal behavior tests on a restraint stress-induced mice model. The elevated plus maze (EPM) test, the light dark exploration (LDE) test, and the open field (OF) test demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 39 publications
2
40
0
1
Order By: Relevance
“…Without a curative drug, people will be anxious about their health when infected. Anxiety activates the hypothalamus-pituitary-adrenal (HPA) axis [ 33 ] and hypersecretion of stress-related hormones, thereby reducing duration of deep sleep and precipitating sleep disturbances [ 34 ]. A study of insomnia of medical staff involved the COVID-19 outbreak found that worry about being infected was related to sleep disorder [ 21 ], which was in line with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Without a curative drug, people will be anxious about their health when infected. Anxiety activates the hypothalamus-pituitary-adrenal (HPA) axis [ 33 ] and hypersecretion of stress-related hormones, thereby reducing duration of deep sleep and precipitating sleep disturbances [ 34 ]. A study of insomnia of medical staff involved the COVID-19 outbreak found that worry about being infected was related to sleep disorder [ 21 ], which was in line with our study.…”
Section: Discussionmentioning
confidence: 99%
“…CHM constituents have been shown to produce antidepressant effects in animal or cell models by antagonizing the CRF 1 receptor [ 9 , 110 , 163 ]. The activity of three major constituents isolated from St. John’s wort, hypericin, pseudohypericin, and hyperforin against the CRF 1 receptor has been examined by measuring their effects on CRF-stimulated cAMP formation [ 163 ].…”
Section: Chm Modulation Of the Hpa Axismentioning
confidence: 99%
“…Accordingly, body weight assessment, sucrose preference test (SPT), forced swimming test (FST) and open field test (OFT) were executed in CUMS-induced rats to analyze the antidepressant effects of CMVO after inhalational administration. Previously, it was shown that CX volatile oil exerts an antidepressant effect by regulating hyperactivity of the HPA axis ( Wang et al, 2018b ), while the main active component of MX volatile oil exerts a neuroprotective effect on the hippocampus ( Zhao et al, 2018 ). In addition, abnormal function of the HPA axis and deficiency of hippocampal monoamine neurotransmitters have been implicated in the pathogenesis of depression ( Chen et al, 2019 ; Xing et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%